ANALISIS PENGARUH DANA PIHAK KETIGA, NON PERFORMING FINANCING, CAPITAL ADEQUACY RATIO, MODAL SENDIRI DAN MARJIN KEUNTUNGAN TERHADAP PEMBIAYAAN MURABAHAH - RATU VIEN SYLVIA AZIZA; ADE SOFYAN MULAZID (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". This study aims to determine the effect review Third Party Fund (DPK), Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Equity and Operating Profit Margin simultaneous or partial Against AT Murabahah Islamic Banks in Indonesia Period 2011-2015, There are nine samples hearts Research singer Yang meet Namely Research Criteria Bank BCA Syariah, BJB Syariah, BNI Syariah, BRI Syariah, Bank Syariah Mandiri, Bukopin Syariah, Bank Muamalat, Panin Syariah, Islamic Victoria. The analysis tool used panel data regression analysis. Model Chosen Was Random Effect Model The tested with F test and t test, with 5% significance. Based on the findings of the test F known that DPK, NPF, CAR, Equity and Operating Profit Margin Financing Murabahah simultaneously affect Against AT Islamic Banks. Based on t test known that Equity and Profit Margin effect against Murabahah, DPK, CAR and influential Against NPF not on Murabahah Commercial Bank Syariah.